Respons Pertumbuhan Bibit Kakao (Theobroma cacao L.) Terhadap Beberapa Komposisi Media Tanam Dan Frekuensi Penyiraman - juan winaldy s; Jonis Ginting; Irsal Irsal (Universitas Sumatera Utara, 2016)
Use proper planting media can support the development of cocoa seeds. But its use should be based on the nature of the medium is able to absorb and hold water in relatively long. Hence required combination some composition media cropping and frequency watering to gain the mass seeds cocoa. This study was conducted in the greenhouse the Faculty Agricultural University of North Sumatra, located at an elevation of above sea level 25 from January 2015 until April 2015, using a random factorial group with two factors the Media Treatment Composition Planted with Topsoil treatment, Topsoil + Compost TKKS (1:2), Topsoil + Manure a Chicken (1:2)Topsoil + Sphagnum (1:2) and Frequency of treatment of Sprinkling with 100%KL/ml/one day, 100%KL/ml/two days, 100%/KL/ml/three days. Parameter examined is tall plant, diameter of the stem, broad leaves, wet weight header, wet roots, dry weight header, and weights dried root. The research results show that composition media planting had have real impact on parameter tall plant, diameter of the stem, wet weight roots and weight dried root. Treatment of frequency watering affect significant a tall parameters,diameter of stem, wet weight roots, and weight dried roort observation.Interaction some composition media cropping and frequency watering do not affect significant a tall parameters observation. Keywords: cocoa, planting media, watering frequency